Analisis Kualitas Instrumen Evaluasi Pembelajaran Menggunakan Media Digitalisasi Untuk Memotivasi Hasil Belajar Peserta Didik - Habib Maulana (LPPM Politeknik Pratama, 2023)
This study aims to analyze the quality of learning evaluation instruments that use digitalization media in order to motivate student learning outcomes. The use of digitalization media in learning has the potential to increase student engagement, increase learning motivation, and better learning outcomes. Therefore, it is important to ensure that the evaluation instrument used is in accordance with the context of using digitalization media. The instrument used to measure students' learning motivation is by using digital media for evaluating learning at the elementary school level, which must be of good quality and have been tested. This study aims to determine the quality of students' learning motivation instruments using digital media for evaluation of fifth grade learning at SD Negeri Pamulian 01 based on content validity, reliability, discriminating power and level of test difficulty. The subjects of this study were lecturers, class teachers and fifth grade students at SD Negeri Pamulian 01. The approach used in this study was descriptive quantitative. Quantitative data analysis techniques were used to determine the quality level of the instrument based on empirical data while qualitative data were used to determine the category level of validity, reliability, discriminatory power and level of test difficulty. The results showed that the quality of students' learning motivation instruments using learning evaluation digitalization media totaling 20 items was 100% valid with a reliability of 0.901 (very good category). Based on the discriminating power test, there are 1 item in the Very Good category, 13 items in the moderate category, 6 items in the good category. Meanwhile, based on the difficulty index of the test, there are 2 items in the easy category, 17 items in the medium category, and only 1 item in the difficult category. Thus, overall the test instrument has good quality and is feasible and can be used to measure students' learning motivation using digital media for evaluation of learning.